Bose–Einstein condensation of 162Dy and 160Dy - Yijun Tang; Nathaniel Q Burdick; Kristian Baumann; Benjamin L Lev (New Journal of Physics, 2015)
We report Bose–Einstein condensation of two isotopes of the highly magnetic element dysprosium: ^162 Dy and $^{160}$ Dy. For ^162 Dy, condensates with 10 ^5 atoms form below T = 50 nK. We find the evaporation efficiency for the isotope ^160 Dy to be poor; however, by utilizing a low-field Fano–Feshbach resonance to carefully change the scattering properties, it is possible to produce a Bose–Einstein condensate of ^160 Dy with 10 ^3 atoms. The ^162 Dy BEC reported is an order of magnitude larger in atom number than that of the previously reported ^164 Dy BEC, and it may be produced within 18 s.